PENERAPAN PROGRAM EDUKASI DAN KETERSEDIAAN ALCOHOL BASED HAND RUB (ABHR) DALAM UPAYA PENINGKATAN PERILAKU PATUH HAND HYGIENE PERAWAT DI RUANG CEMARA I RS. BHAYANGKARA TK. 1 R. SAID SUKANTO - Nur Fitriah Efendy (2022)
Hand hygiene has been recognized as most effective action to preventing and controlling infection. The low compliance of health care workers in hand hygiene practices become a global problem that needs various efforts to improve it. WHO has introduced multimodal strategies that are considered to achieve a good hand hygiene. It was found that 10 nurses (76,9%) did not compliance with hand hygiene while 3 other people (23,1%) complied. Then intervention of education program and the available of ABHR was carried out. Post test was conducted to determine the effectiveness of the intervention carried out. Post test results as many as 8 people (61.5%) were obedient while 5 other people (38.5%) were not. ABHR is placed in several strategic places such as the nurse station and the action desk. It can be stated that giving intervention by educational program and availability ABHR can improve compliance hand hygiene among nurses